Effects of hemodialysis adequacy on chronic kidney disease complications using latent class trajectory modeling: a real-world study based on long-term observation of Kt/V - Ai, Sanxi; Xu, Qiuyu; Chen, Gang; Zheng, Ke; Qin, Yan; Li, Xuemei (Frontiers in Medicine, 2024)
Introduction: Previous studies on hemodialysis adequacy primarily focused on the association between Kt/V and survival, and low Kt/V is associated with increased mortality. There is a paucity of research on the correlation between Kt/V and chronic kidney disease (CKD) complications.: The retrospective study was conducted in the blood purification center of a tertiary hospital in China from July 2020 to September 2022. It aimed to analyze the association between latent Kt/V trajectory categories and CKD complications (hypertension, anemia, mineral, and bone disorder) and inflammatory markers. The latent class trajectory model was established to describe the different patterns of Kt/V patient changes over the observation period.Results: During the 2-year study period, 93 patients on thrice-weekly hemodialysis with residual kidney function < 2 ml/min were included. In the 3-class Kt/V trajectory model, 21 patients were in class 1 with a Kt/V trajectory that declined from a higher to lower levels (from > 1.6 to < 1.4), 59 patients were in class 2 with Kt/V consistently in a relatively low range (around 1.4), and 13 patients were in class 3 with Kt/V stabilized around 1.6. No significant difference in CKD complications or inflammation markers was observed among the three Kt/V trajectories.Under the premise of adequate Kt/V, neither a stable higher Kt/V nor a declined Kt/V significantly influenced CKD complications or inflammatory markers.